Akuttherapie des ischämischen Schlaganfalls - Hussain, Muadh; Purrucker, Jan; Ringleb, Peter A.; Schönenberger, Silvia (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2025)
Intravenous thrombolysis (IVT) and endovascular therapy (EVT) are the cornerstones of acute ischemic stroke treatment. While IVT has been an integral part of acute therapy since the mid-1990s, EVT has evolved as one of the most effective treatments in medicine over the past decade. Traditionally, systemic thrombolysis has been performed with alteplase (rtPA). More recently, tenecteplase (TNK) has been shown to be non-inferior to rtPA. TNK has some pharmacological advantages over rtPA and may lead to earlier recanalization, particularly in large vessel occlusions. All recanalization therapies are highly time dependent. To ensure rapid treatment, standard operating procedures (SOPs) should be established and followed in clinical practice. The optimal time window for IVT is 4.5 h after symptom onset and can be extended up to 9 h using specialized imaging techniques. For EVT, studies suggest a time window up to 24 h after symptom onset. In some cases, EVT has been successfully performed beyond this time window. To select patients for EVT, advanced imaging identifying salvageable brain tissue might be necessary. Even in large ischemic stroke, EVT can still improve outcome. Compared to EVT, IVT requires fewer technical and human resources, so more stroke patients can potentially be treated. In contrast, EVT requires highly trained personnel with sophisticated equipment and can, therefore, only be performed in specialized centers. Both procedures should be combined within the 4.5 h time window for patients without contraindications.